Determination of the Mg/Mn ratio in foraminiferal coatings: An approach to correct Mg/Ca temperatures for Mn-rich contaminant phases - Hasenfratz, AP; Martínez-García, A; Jaccard, SL; Vance, D; Wälle, M; Greaves, M; Haug, GH (Elsevier BV, 2017)
The occurrence of manganese-rich coatings on foraminifera can have a significant effect on their bulk Mg/Ca ratios thereby biasing seawater temperature reconstructions. The removal of this Mn phase requires a reductive cleaning step, but this has been suggested to preferentially dissolve Mg-rich biogenic carbonate, potentially introducing an analytical bias in paleotemperature estimates. In this study, the geochemical composition of foraminifera tests from Mn-rich sediments from the Antarctic Southern Ocean (ODP Site 1094) was investigated using solution-based and laser ablation ICP-MS in order to determine the amount of Mg incorporated into the coatings. The analysis of planktonic and benthic foraminifera revealed a nearly constant Mg/Mn ratio in the Mn coating of ∼0.2 mol/mol. Consequently, the coating Mg/Mn ratio can be used to correct for the Mg incorporated into the Mn phase by using the down core Mn/Ca values of samples that have not been reductively cleaned. The consistency of the coating Mg/Mn ratio obtained in this study, as well as that found in samples from the Panama Basin, suggests that spatial variation of Mg/Mn in foraminiferal Mn overgrowths may be smaller than expected from Mn nodules and Mn–Ca carbonates. However, a site-specific assessment of the Mg/Mn ratio in foraminiferal coatings is recommended to improve the accuracy of the correction. We acknowledge the financial support provided by ETH Research Grant ETH-04 11-1 (A.P.H.), and the Swiss National Science Foundation grants PZ00P2_141424 (A.M.-G.) and PP00P2_144811 (S.L.J.). This work was also funded (in part) by The European Research Council (ERC grant 2010-NEWLOG ADG-267931 HE).